Working Capital Financing Preferences: The Case of Mauritian Manufacturing Small and Medium Sized Enterprises (SMEs) - Kesseven Padachi; Carole Howorth; M. S. Narasimhan (Asian Academy of Management Journal of Accounting and Finance, 2012)
This paper investigates the approach of small- to medium-sized Mauritian manufacturing firms to working capital finance using a survey-based approach and case studies. Financing has been cited as one of the most common problems faced by SMEs and is often viewed as one of their main barriers to growth. Using parametric and nonparametric techniques, the important variables that affect the demand for financing are examined. Interestingly, it is observed that the sample firms adopted more informal sources of financing and networking to meet their financing requirements. The financing preferences of the firms were predominantly short-term and there was conclusive evidence that they were reluctant to move down the pecking order for fear of losing control of their businesses. The findings confirmed that internal resources, non-bank sources and short-term debt represent the main sources of financing. The research findings provided some new evidence in support of the different approaches to financing working capital. These SMEs used more informal sources such as shareholder loans and bootstrap finance. These results indirectly suggest that firms experience significant information costs that prevent them from gaining access to the traditional sources of financing. The findings of the study will be useful to the financial institutions that fund SMEs and to policy makers.